Evaluation of compression and pull-out strengths of the callus induced by autogenous cortical and cancellous bone grafting in dogs - Saat, Emine; Durmuş, Ali Said (KAFKAS UNIVERSITY, 2009)
The aim of this study was to compare the pull and push resistance values of callus resulting from administration of autogenous cortical and cancellous bone grafts for the repairment of bone defects in dogs. Experiment was carried out on 12 female different breeds of dogs weighing between 25-30 kg and aged between 2-3 years. Under general anesthesia, a 0.7 cm segmental defect was performed in a right or left radius of dogs. The defects formed have been filled with autogenous cancellous bone graft in 6 dogs and with autogenous cortical bone graft in 6 dogs. At the ends of the 2nd, 4th and 6th months two dogs of each group were sacrificed, grafted bones removed and the push and pull tests were performed. Test results showed that the push and pull values of the autogenous cancellous bone grafts were higher than those values of the autogenous cortical bone grafts.
Köpeklerde otojen kortikal ve spongiyöz kemik greftlerinin uygulanması ile oluşan kallusun çekme ve basma dayanımlarının i?ncelenmesi
Keywords: Autogenous cortical and cancellous bone grafts; Compression and pull-out strengths; Dog; Healing